Effect of Anterior Nasal Packing on Eustachian Tube Function and Middle Ear Pressure - Rahim, Md Manjur; Taous, Ahmmad; Zafar, Md Hasan; Islam, Mozharul; Asad, Khalid; Ali, Md Tayob (Bangladesh Journal of Otorhinolaryngology, 2020)
The present study includes evaluation 60 ears of 30 nasal patients admitted to department of Otolaryngology and Head-Neck Surgery at Banghabandhu Sheikh Mujib Medical University. Each patient underwent nasal surgery followed by anterior nasal packing for 48 hours. All patients were investigated by tympanometry prior to surgery, 2nd post operative day before pack removal and on 7th post operative day 5 days after pack removal. This study shows that nasal packing result in Eustachian tube dysfunction and negative middle ear pressure which is reversible in nature. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 27-31